Strategi Pengembangan Kepribadian Pendidik Pendidikan Agama Islam dan Implikasinya terhadap Proses Pembelajaran - Ermansyah Ermansyah; Fadriati Fadriati (YASIN, 2026)
Although the development of Islamic Religious Education (PAI) educators’ personality has received attention in previous studies, research that specifically examines strategies for developing PAI educators’ personality and its direct implications for the learning process in formal educational settings remains relatively limited. This study aimed to analyze strategies for developing the personality of PAI educators and their implications for the learning process. Employing a qualitative approach with a case study design, the study involved ten PAI educators and supporting informants selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and document analysis, and were then examined using thematic analysis. The findings show that strategies for developing the personality of PAI educators are implemented through the habituation of religious values, self-reflection, and continuous professional development. These strategies lead to the creation of a conducive learning climate, the enhancement of the quality of pedagogical interactions, and positive student responses during the learning process. The findings contribute to the development of theoretical perspectives on educators’ personality competence within Islamic education and broaden understanding of the role of teacher personality as a strategic factor in PAI learning. The study concludes that systematic and continuous development of PAI educators’ personality is essential and encourages educational institutions and policymakers to design teacher development programs that integrate pedagogical, professional, and personality dimensions. The implications of this research include theoretical contributions to enriching the literature on Islamic education and practical implications for schools and educational institutions in improving the quality of PAI learning, while also opening opportunities for further exploration of institutionally grounded intervention models for developing the personality of PAI educators.